Gigantic blue shift of two-photon–induced photoluminescence of interpenetrated metal–organic framework (MOF) - Chen Zhihui; Xu Defeng; Zhu Menglong; Wang Yueting; Feng Junfan; Shu Chuancun; Xiao Si; Meng Jianqiao; He Jun (Nanophotonics, 2023)
As an important means of modern science and technology, multiphoton fluorescence plays an essential role in high-resolution imaging, photochemistry, micro- and nano-processing and clinical diagnosis. Multiphoton fluorescence usually shares the same radiative channel as its intrinsic fluorescence. Under multiphoton excitation, except for red shift fluorescence caused by the reabsorption effect, gigantic blue shift of multiphoton fluorescence is rarely reported. In this work, metal–organic frameworks (MOFs) with 7-fold and 8-fold interpenetration are successfully synthesized. The synthesized 8-fold interpenetrated MOFs show unexpectedly giant blue-shifted (∼40 nm) two-photon–induced fluorescence compared with its fluorescence emission. Specific optical selection rules lead to different final transition states in one-photon absorption and two-photon absorption. The density functional theory (DFT) and time-dependent density functional theory (TDDFT) simulations show that, under two-photon excitation, electrons and holes can be more delocalized, and intermolecular interactions mainly govern the emission process of 8-fold interpenetrated MOFs. Highly excited electronic states of the interpenetrated MOFs are effectively excited and emitted under two-photon excitation, thus generating the inevitable blue-shifted two-photon–induced fluorescence emission. Our work provides a guide for exploring the excitation mechanism of fluorescent MOFs and offers an access to a tunable all-optical single-crystal device.